2019
DOI: 10.1371/journal.pone.0213615
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with false-positive mammography at first screen in an Asian population

Abstract: IntroductionFalse-positive recall is an issue in national screening programmes. The aim of this study is to investigate the recall rate at first screen and to identify potential predictors of false-positive recall in a multi-ethnic Asian population-based breast cancer screening programme.MethodsWomen aged 50–64 years attending screening mammography for the first time (n = 25,318) were included in this study. The associations between potential predictors (sociodemographic, lifestyle and reproductive) and false-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 43 publications
0
11
0
Order By: Relevance
“…While national mammography screening programmes have been widely implemented and shown to be cost effective in countries including the US [ 6 ], Australia [ 7 ], and South Korea [ 8 ], their respective guidelines for screening still vary. The current strategy in Singapore has its limitations, such as poor attendance, with only 66% of women aged 50 to 69 ever getting a mammogram in 2018; as well as high false positive rates and missed cases [ 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…While national mammography screening programmes have been widely implemented and shown to be cost effective in countries including the US [ 6 ], Australia [ 7 ], and South Korea [ 8 ], their respective guidelines for screening still vary. The current strategy in Singapore has its limitations, such as poor attendance, with only 66% of women aged 50 to 69 ever getting a mammogram in 2018; as well as high false positive rates and missed cases [ 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Ultimately a solid tissue biopsy is taken for histopathology to provide a definitive diagnosis, of which a recent study showed 93.8% of cases proved benign. This means that for a single breast cancer case identified by mammography, 15 women without cancer were subjected to unnecessary invasive procedures [ 6 ]. Moreover, as an independent diagnostic tool for early-stage disease or aggressive malignancies, imaging techniques are generally limited as they have a reduced threshold of detection in dense breasts and are less sensitive to small tumors [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…The American Cancer Society advises annual mammography screening beginning from the age of 45 [9], while South Korea recommends mammography screening every two years from the age of 40 [10]. The current strategy in Singapore has its limitations, such as poor attendance, with only 66% of women aged 50 to 69 ever getting a mammogram in 2018 [11]. It was observed that half of these women do not come back for regular screening at two-year intervals.…”
Section: Introductionmentioning
confidence: 99%
“…It was observed that half of these women do not come back for regular screening at two-year intervals. This lukewarm response to mammogram screening may be due to the high potential for false-positive results and unnecessary biopsies [11]. Furthermore, the recommended screening commencement age of 50 may be inadequate as breast cancer can develop before that.…”
Section: Introductionmentioning
confidence: 99%